Earnings persistence, earnings power, and equity valuation in consumer goods firms - Nurani Fatma; Widi Hidayat (Emerald Publishing Limited, 2019)
The purpose of this paper is to examine the influence of earnings persistence and earnings power on equity valuation.The purposive sampling method was applied to determine the samples of selected 100 firms. This study employed secondary data obtained from the annual reports and financial statements of consumer goods firms listed on the Indonesian Stock Exchange for the period 2010–2014. The analysis technique used a multiple regression analysis.The study result shows that, partially, earnings persistence and earnings power affect equity valuation by investors. Earnings persistence has a negative influence, whereas earnings power has a positive influence on equity valuation.This study throws additional lights on equity valuation specific to consumer goods industries.